A Study Of Performance Appraisal In A Total Quality Management (TQM) Cultured Organization - Long, Theng Chao (2006)
This research paper examines the employees' perception of performance appraisal characteristics on the performance appraisal systems in a Total Quality Management cultured organization in Malaysia. The performance appraisal characteristics being studied are appraisal frequency, appraisal form, appraisal process, ratee participation, carrer development and appraisal effectiveness.